Czy w Nowym Muzeum Historii Zagłady Yad Vashem znajdziemy „Innego”? - Goldberg, Amos (Zagłada Żydów. Studia i Materiały, 2011)
The essay analyzes the main exhibition of Yad Vashem New Holocaust Museum (opened in 2005) as a historical narrative, with particular criticism directed at the forms of narration used. According to the author, the main problem is that the museum’s narration excludes all otherness – it lacks context (only fragmentary historical background of World War II was presented), historical genesis (with the exception of anti-Semitism), real perpetrators, real victims experiencing trauma, discussion of the life of the post-war Diaspora and the topic of non-Jewish victims.